2017
DOI: 10.1111/jbg.12299
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study and annotating candidate gene networks affecting age at first calving in Nellore cattle

Abstract: We performed a genome-wide mapping for the age at first calving (AFC) with the goal of annotating candidate genes that regulate fertility in Nellore cattle. Phenotypic data from 762 cows and 777k SNP genotypes from 2,992 bulls and cows were used. Single nucleotide polymorphism (SNP) effects based on the single-step GBLUP methodology were blocked into adjacent windows of 1 Megabase (Mb) to explain the genetic variance. SNP windows explaining more than 0.40% of the AFC genetic variance were identified on chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 29 publications
0
34
2
Order By: Relevance
“…Among the genes identified in this study, NMNAT1 and NCOA2 appear to be associated with female fertility via regulation of the secretion of luteinizing hormone and follicle development in cattle (Mota et al . ). Experiments on mice revealed that Arntl ( Bmal1 ) knockout individuals were infertile and that the genes were required for testosterone production (Alvarez et al .…”
Section: Resultsmentioning
confidence: 97%
“…Among the genes identified in this study, NMNAT1 and NCOA2 appear to be associated with female fertility via regulation of the secretion of luteinizing hormone and follicle development in cattle (Mota et al . ). Experiments on mice revealed that Arntl ( Bmal1 ) knockout individuals were infertile and that the genes were required for testosterone production (Alvarez et al .…”
Section: Resultsmentioning
confidence: 97%
“…Non-overlapping islands within the lineages were explored for gene content and among the genes identified within the regions we can highpoint those described in Table 5 . Remarkably, six genes were also reported in Nellore-specific studies associated with carcass traits [ 64 ] ( PPM1 ), age at first calving [ 65 ] ( NPBWR1, OPRK1, and MRPL1 ), and birth weight [ 66 ] ( RPS20 and TGS1 ).…”
Section: Discussionmentioning
confidence: 98%
“…The region presents tropical climate with dry winter season, commonly known as a savannah climate, in which each month has an average temperature above 18°C and a rainfall index of up to 1,200 mm (Sá Júnior, Carvalho, Silva, & Carvalho Alves, ). Contemporary groups were composed by the combination of year and season of birth as proposed by Mota et al ().…”
Section: Methodsmentioning
confidence: 99%